Pembuatan Teh Herbal Campuran Kelopak Bunga Rosella (Hibiscus sabdariffa) dan Herba Seledri (Apium graveolens) - Munim, Abdul; Hanani, Endang; Mandasari, Andita (Majalah Ilmu Kefarmasian, 2008)
Rosella calyx (Hibiscus sabdariffa) has been reported exhibited on decreasing high blood pressure activity. Celery herb (Apium graveolens) has been acknowledged as an antihypertension herb with vasodilator and diuretic effect. Combination of the extracts was expected to provide synergism effect on decreasing high blood pressure. This study was intended to prepare the combination of herbal tea from standardized extracts of rosella calyx and celery herb. Standardization of rosella calyx and celery herb included determination of several specific and non-specific parameters. Three different formulas of herbal tea were prepared that would be hedonically tested to obtain the most favorable herbal tea formula from the 30 panelists. The most favorable formula was formula C which contained rosella calyx (2 gram) and celery herb (0.5 gram).